INTERDISCIPLINARY APPROACH TO LINGUISTIC WORDS AND SOUNDS - Abdukarimova Dildora Zafarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The paper work we describe an interdisciplinary approach entails pulling appropriately from various disciplines (or independent branches of learning or domains of competence) to redefine challenges beyond usual limits and arrive at solutions based on a new understanding of complex situations.